Botulinum Toxin Type A Versus Placebo for Idiopathic Clubfoot: A Two-Center, Double-Blind, Randomized Controlled Trial. (19th September 2018) - Alvarez, Christine M.; Wright, James G.; Chhina, Harpreet; Howren, Alyssa; Law, Peggy
Abstract : Background: Congenital idiopathic clubfoot is a condition that affects, on average, approximately 1 in 1, 000 infants. One broadly adopted method of management, described by Ponseti, is the performance of a percutaneous complete tenotomy when hindfoot stall occurs. The use of onabotulinum toxin A (BTX-A) along with the manipulation and cast protocol described by Ponseti has been previously reported. Our goal was to compare the clinical outcomes between BTX-A and placebo injections into the gastrocnemius-soleus muscle at the time of hindfoot stall in infants with idiopathic clubfoot treated with the Ponseti method of manipulation and cast changes. Methods: This was a double-blind, placebo-controlled, parallel-group study with balanced randomization. Results: At 6 weeks after the study injection (T1), 66% of the 32 feet in the BTX-A arm and 63% of the 30 in the placebo arm responded to the treatment (i.e., obtained ≥15° of dorsiflexion). Seven of the 11 patients in the BTX-A arm and all of the 11 in the placebo arm who had not responded at T1 responded to a rescue BTX-A injection at 12 weeks after the first injection (T2). The combined response rate at T2, which included the first-time responders as well as the patients who did not respond at T1 but did at T2, was 88% in the BTX-A arm and 100% in the placebo arm, culminating in a 94% response rate at T2. At T3 (2 years of age), 89% of the feet continued to respond and there was an 8% surgical rate. Conclusions: There was no difference in outcomes between the BTX-A and placebo groups when the injection was performed at the time of hindfoot stall. Overall, 92% of the clubfeet in this study responded to a manipulation and cast protocol alone, with or without BTX-A injection, by 12 weeks after hindfoot stall, or we can say that 92% of the clubfeet did not require percutaneous Achilles tendon lengthening by 2 years of age. The need for tenotomy is limited to those who have not responded to treatment at this point, and the need for surgery is limited to those for whom all attempts at treatment with sequential casts, BTX-A, and percutaneous Achilles tendon lengthening have failed. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.